2007
DOI: 10.1124/dmd.107.016089
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Enzymes and Transporters Induced by Anti-Human Immunodeficiency Virus Protease Inhibitors in Human Hepatocytes: Implications for Predicting Clinical Drug Interactions

Abstract: ABSTRACT:Although many of the clinically significant drug interactions of the anti-human immunodeficiency virus (HIV) protease inhibitors (PIs) can be explained by their propensity to inactivate CYP3A enzymes, paradoxically these drugs cause (or lack) interactions with CYP3A substrates that cannot be explained by this mechanism (e.g., alprazolam). To better understand these paradoxical interactions (or lack thereof), we determined the cytochromes P450 and transporters induced by various concentrations (0-25 M)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 32 publications
7
101
3
Order By: Relevance
“…The relationship between breast cancer and the CYP gene family was recently reported, including CYP1B1 (Economopoulos and Sergentanis, 2010;Ozbek et al, 2010), CYP2J2 (Jiang et al, 2007(Jiang et al, , 2009), CYP2D6 (Stingl et al, 2010;González-Tejera et al, 2010;Thompson et al, 2011), CYP2C8 (Knüpfer et al, 2004;Dixit, et al, 2007;Jernström et al, 2009), CYP2C9 (Ekhart et al, 2008;Jernström et al, 2009) and CYP2C19 (Justenhoven et al, 2009;Ruiter et al, 2010;Goetz and Suman, 2010). Several studies have reported different conclusions for the relationship with CYP2C19.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between breast cancer and the CYP gene family was recently reported, including CYP1B1 (Economopoulos and Sergentanis, 2010;Ozbek et al, 2010), CYP2J2 (Jiang et al, 2007(Jiang et al, , 2009), CYP2D6 (Stingl et al, 2010;González-Tejera et al, 2010;Thompson et al, 2011), CYP2C8 (Knüpfer et al, 2004;Dixit, et al, 2007;Jernström et al, 2009), CYP2C9 (Ekhart et al, 2008;Jernström et al, 2009) and CYP2C19 (Justenhoven et al, 2009;Ruiter et al, 2010;Goetz and Suman, 2010). Several studies have reported different conclusions for the relationship with CYP2C19.…”
Section: Discussionmentioning
confidence: 99%
“…in a dose-dependent manner. A 12% decrease of ritonavir exposure is already seen with doses of 400mg daily and exposure further decreased by 45% with ritonavir 1000mg/d [19] An increase of cytochrome 2C9, 2C19 and 1A2 activity by ritonavir was shown in human hepatocytes [15] as well as under long term treatment with lopinavir boosted with 200mg ritonavir daily in healthy volunteers [16]. As CYP2C9 and CYP1A2 are involved in albendazole and albendazole sulfoxide metabolism [22], their induction by long term ritonavir administration of 400mg daily could explain a lower bioavailability of albendazole.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, interaction of protease inhibitors with drugs that are cleared predominantly by CYP3A enzymes are profound and clinically significant [14]. It is still equivocal whether long-term administration of ritonavir may also lead to a certain induction of CYP3A enzymes [15]. However, studies both in healthy volunteers [16] and patients [17] do not support CYP3A4 induction.…”
Section: Introductionmentioning
confidence: 99%
“…Protease inhibitors are metabolised by the cytochrome P450 system. They may inhibit or induce the system and alter the [61]. Indeed, paclitaxel exposure (the area under curve) is increased in patients receiving protease inhibitors.…”
Section: Differential Diagnosismentioning
confidence: 99%